2019
DOI: 10.1016/j.jfoodeng.2018.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Generation of magnesium enriched water-in-oil-in-water food emulsions by stirred cell membrane emulsification

Abstract: Highlights • PGPR was used to stabilise internal water droplet interface • Starch and pea protein isolate were used to stabilise w 1 /o droplet interface • Low energy membrane emulsification process generated stable w 1 /o/w 2 emulsions • Variation of shear stress and injection rate produced drops between 35 and 320 µm • Complex food emulsifiers delayed release of Mg 2+ ions for up to 2 weeks

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Emulsions were initially processed with a high speed mixer. Then, emulsions were also processed via a previously reported stirred cell membrane emulsification, 34 thereby removing droplet size variation as a factor impacting aroma release. Since our initial analysis of the high speed processed emulsions suggested that droplet creaming, which was observed for all emulsions produced, might have affected aroma release, creaming was suppressed in the membrane processed emulsions by adding the viscosifying agent xanthan gum.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Emulsions were initially processed with a high speed mixer. Then, emulsions were also processed via a previously reported stirred cell membrane emulsification, 34 thereby removing droplet size variation as a factor impacting aroma release. Since our initial analysis of the high speed processed emulsions suggested that droplet creaming, which was observed for all emulsions produced, might have affected aroma release, creaming was suppressed in the membrane processed emulsions by adding the viscosifying agent xanthan gum.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The composition of all liquid samples is listed in Table . Two hydrophilic emulsifiers including the LMW surfactant Tween 20 , and the polymeric emulsifier OSA starch , to stabilize the external w/o/w emulsion interface were selected in this study to assess the interaction of hydrophilic emulsifier type with aroma compounds and its impact on dynamic aroma release. PGPR was chosen as the hydrophobic emulsifier due to most successfully stabilizing w/o/w emulsions .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different ME approaches are illustrated to produce double emulsions, such as stirred cell ME and premix ME (Figure 2a). Pu et al (2019) applied complex food emulsifiers (referring to starch and protein) to fabricate W/O/W emulsions with similar average droplet diameters and high encapsulation rates by stirred cell emulsification. Premix ME is to pass the coarse double emulsion through the membrane to reduce the droplet size and obtain the fine double emulsion with more uniform particle size distribution (Vladisavljevic, 2019).…”
Section: Membrane Emulsification (Me)mentioning
confidence: 99%
“…Moreover, the sizes of oil droplets are also determined by processing parameters that are related to the fabrication methods (Chouaibi et al., 2019). For example, as mentioned before, ME requires less shear stress, and microfluidic emulsification includes different precisely controllable systems (co‐flow, T‐connection, and flow focusing), allowing the preparation of smaller and more uniform droplets (Pu et al., 2019; Yousofvand & Ghasemi, 2022). Moreover, the experiment has performed that the type and concentration of surfactant, stirring time and rate, components of different phases, properties of inner water droplets, and viscosity ratio of continuous phase to dispersed phase are closely related to the size of droplets (Oppermann et al., 2018).…”
Section: Stability Of Double Emulsionsmentioning
confidence: 99%